Perilaku Makan Dan Status Gizi Anak Usia Pra Sekolah Di Desa Mangkung Kecamatan Praya Barat Lombok Tengah - Baiq Pathiyah; Abdul Salam; Susilo Wirawan; Iketut Swiryajaya (Poltekkes Kemenkes Mataram, 2018)
Background. At the age of pre-school children entered the phase of negavistik i.e. children to refuse food offered, as a result of the child will behave deviate. This study to find out the description of the behaviour of pre-school age children eat in the village of Mangkung sub-district of Praya Barat. Research Methods. Examination is a descriptive observational. This research was conducted in the village of Mangkung sub-district of Praya Barat by way of free variables and bound variables obtained through observation, measurement, recording and analysis of data. Research Result. Results from the research conducted that could result with the behavior of feeding, nutritional status and consumption pre school aged children. Eating behavior level samples that belonged to good 27 people with persentage 40 .9 good nutrient that is 61 status with persentage 92,4 people and levels of consumption of the protein that has the above protein samples adequacy of as many as 60 people (90.9) and the level of energy consumption samples that have energy above the adequacy of as many as 36 people (54.5). Conclusion. Ari results research conducted that may be known to the behavior of eating and nutritional status of pre school age children in the village of Mangkung sub-district of Praya Barat central of Lombok